Pengaruh Viral Marketing, Celebrity Endorser dan Brand Image terhadap Purchase Decision: (Studi Pada Pengguna Scarlett Whitening di Denpasar) - Gotama, Putu Sieny Aprillisia; Agustina, Made Dian Putri; Suasti Puja, I Made (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Teìchnological deìveìlopmeìnts and increìasingly wideìspreìad inteìrneìt peìneìtration haveì changeìd theì markeìting landscapeì significantly, giving riseì to a neìw paradigm that combineìs various eìleìmeìnts, including onlineì markeìting, viral markeìting and ceìleìbrity eìndorseìmeìnt. Onlineì markeìting is beìcoming theì main foundation in this eìra, wheìreì companieìs not only utilizeì  theìir weìbsiteìs but also various  social platforms and seìarch eìngineìs to reìach  theìir audieìnceì. Theì purposeì of this study is to deìteìrmineì theì influeìnceì of viral markeìting, ceìleìbrity eìndorseìrs and brand imageì on purchasing deìcisions. Theì location of this study was conducteìd in Deìnpasar City and theì sampleì useìd was 150 reìspondeìnts. Theì data analysis teìchniqueìs useìd areì Validity Teìst, Reìliability, Classical Assumptions, Multipleì Lineìar Reìgreìssion, Coeìfficieìnt of Deìteìrmination, t Teìst and F Teìst. Baseìd on theì reìsults of theì study, it can beì seìeìn that viral markeìting has a significant positiveì eìffeìct on purchasing deìcisions, ceìleìbrity eìndorseìrs haveì a significant positiveì eìffeìct on purchasing deìcisions, brand imageì Positiveìly influeìnceì significant on purchasing deìcisions and simultaneìously viral markeìting, ceìleìbrity eìndorseìrs and brand imageì haveì a significant influeìnceì on purchasing deìcisions. Theì adviceì that can beì giveìn by reìseìarcheìrs is that Scarleìtt Whiteìning is eìxpeìcteìd to always provideì products that haveì beìneìfits in accordanceì with consumeìr neìeìds, offeìr quality products, collaborateì with artists who areì ableì to narrow promotional meìssageìs weìll and makeì products that areì supeìrior to compeìtitors.